Dare et habere - Marina, Gazzini (Reti Medievali E-Book, 2002)
The Italian cities of the last centuries of the Middle Ages continued to witness - alongside a progressive crystallisation of the social hierarchies - the economic and social ascent of individuals belonging to the 'middle class'. These were homines novi who, without resorting to dynastic connections and often rejecting the associative model of the guilds, managed to build fortunes and dignity through trade, enterprise, the exploitation of the land, the solidarity of district and parish and the management of welfare. Emblematic of such careers is the figure of an economic agent originating from the rural district, Donato Ferrario da Pantigliate, who in 1429 founded in Milan a devotional and welfare institute, the Scuola della Divinità. The book reconstructs the social, economic and spiritual conduct of Donato, placing it within the urban context of Milan in the first half of the fifteenth century.